Zinc tolerant plant growth promoting bacteria alleviates phytotoxic effects of zinc on maize through zinc immobilization - Devendra Jain (Nature Portfolio, 2020)
Abstract The increasing heavy metal contamination in agricultural soils has become a serious concern across the globe. The present study envisages developing microbial inoculant approach for agriculture in Zn contaminated soils. Potential zinc tolerant bacteria (ZTB) were isolated from zinc (Zn) contaminated soils of southern Rajasthan, India. Isolates were further screened based on their efficiency towards Zn tolerance and plant growth promoting activities. Four strains viz. ZTB15, ZTB24, ZTB28 and ZTB29 exhibited high degree of tolerance to Zn up to 62.5 mM. The Zn accumulation by these bacterial strains was also evidenced by AAS and SEM–EDS studies. Assessment of various plant growth promotion traits viz., IAA, GA3, NH3, HCN, siderophores, ACC deaminase, phytase production and P, K, Si solubilization studies revealed that these ZTB strains may serve as an efficient plant growth promoter under in vitro conditions. Gluconic acid secreted by ZTB strains owing to mineral solubilization was therefore confirmed using high performance liquid chromatography. A pot experiment under Zn stress conditions was performed using maize (Zea mays) variety (FEM-2) as a test crop. Zn toxicity reduced various plant growth parameters; however, inoculation of ZTB strains alleviated the Zn toxicity and enhanced the plant growth parameters. The effects of Zn stress on antioxidant enzyme activities in maize under in vitro conditions were also investigated. An increase in superoxide dismutase, peroxidase, phenylalanine ammonia lyase, catalase and polyphenol oxidase activity was observed on inoculation of ZTB strains. Further, ZIP gene expression studies revealed high expression in the ZIP metal transporter genes which were declined in the ZTB treated maize plantlets. The findings from the present study revealed that ZTB could play an important role in bioremediation in Zn contaminated soils.